Analysis of Aerodynamic Noise Characteristics of High-Speed Train Pantograph with Different Installation Bases - Yongfang Yao; Zhenxu Sun; Guowei Yang; Wen Liu; Prasert Prapamonthon (Applied Sciences, 2019)
The high-speed-train pantograph is a complex structure that consists of different rod-shaped and rectangular surfaces. Flow phenomena around the pantograph are complicated and can cause a large proportion of aerodynamic noise, which is one of the main aerodynamic noise sources of a high-speed train. Therefore, better understanding of aerodynamic noise characteristics is needed. In this study, the large eddy simulation (LES) coupled with the acoustic finite element method (FEM) is applied to analyze aerodynamic noise characteristics of a high-speed train with a pantograph installed on different configurations of the roof base, i.e. flush and sunken surfaces. Numerical results are presented in terms of acoustic pressure spectra and distributions of aerodynamic noise in near-field and far-field regions under up- and down-pantograph as well as flushed and sunken pantograph base conditions. The results show that the pantograph with the sunken base configuration provides better aerodynamic noise performances when compared to that with the flush base configuration. The noise induced by the down-pantograph is higher than that by the up-pantograph under the same condition under the pantograph shape and opening direction selected in this paper. The results also indicate that, in general, the directivity of the noise induced by the down-pantograph with sunken base configuration is slighter than that with the flush configuration. However, for the up-pantograph, the directivity is close to each other in Y-Z or X-Z plane whether it is under flush or sunken roof base condition. However, the sunken installation is still conducive to the noise environment on both sides of the track.